2016
DOI: 10.1021/acsbiomaterials.6b00032
|View full text |Cite
|
Sign up to set email alerts
|

Active Release of Nitric Oxide-Releasing Dendrimers from Electrospun Polyurethane Fibers

Abstract: The fabrication of electrospun composite polyurethane fibers capable of dual-action antibacterial dendrimer release is reported. Generation 4 (G4) poly(amidoamine) dendrimers were functionalized with octyl alkyl chain or quaternary ammonium (QA) moieties followed by modification of the resulting secondary amines with N-diazeniumdiolate nitric oxide (NO) donors to produce dual-action antibacterial dendrimers. Control and NO-releasing dendrimers were doped into polyurethane solutions prior to electrospinning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Worley et al subsequently developed dual‐action antibacterial polyurethane fibers containing biocidal quaternary ammonium and NO‐releasing poly(amidoamine) dendrimers. Using two biocides improved the antibacterial efficacy and reduced the risk of resistance by way of multiple mechanistic bacterial eradication pathways . The authors reported a 4‐log reduction in bacterial viability for both Gram‐negative ( E. coli and P. aeruginosa ) and Gram‐positive ( S. aureus and methicillin‐resistant S. aureus ) bacteria.…”
Section: Exogenous Nitric Oxide For Chronic Wound Therapymentioning
confidence: 99%
“…Worley et al subsequently developed dual‐action antibacterial polyurethane fibers containing biocidal quaternary ammonium and NO‐releasing poly(amidoamine) dendrimers. Using two biocides improved the antibacterial efficacy and reduced the risk of resistance by way of multiple mechanistic bacterial eradication pathways . The authors reported a 4‐log reduction in bacterial viability for both Gram‐negative ( E. coli and P. aeruginosa ) and Gram‐positive ( S. aureus and methicillin‐resistant S. aureus ) bacteria.…”
Section: Exogenous Nitric Oxide For Chronic Wound Therapymentioning
confidence: 99%
“…Worley et al reported the fabrication of electrospun composite polyurethane fibers containing NOreleasing PAMAM den drimers. [99] The fibers exhibited porosity and water adsorption capacities that should enable dynamic gas and fluid exchange, requirements for effective wound dressings. The release of NO releasing PAMAM dendrimers facilitated antibacterial action.…”
Section: Formulationmentioning
confidence: 99%
“…The authors were able to fully characterize 64 armed dendrimers with the ability to deliver large, precise amounts of NO and were shown to be highly antimicrobial [18]. These types of macromolecules have then been applied to biomaterials such as polyurethane nanofibers as potential wound dressing as NO has been also to promote reendothelialization as well [19]. While this type of NO-releasing molecule is excellent for targeted therapeutics, it would be costly to integrate a large quantity of these dendrimers into polymer matrices.…”
Section: Introductionmentioning
confidence: 99%